1999
DOI: 10.1016/s0014-5793(99)00054-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive channel functions to alleviate the cell lysis of marine bacterium, Vibrio alginolyticus, by osmotic downshock

Abstract: The mechanosensitive channel with large conductance of Escherichia coli is the first to be cloned among stretchactivated channels. Although its activity was characterized by a patch clamp method, a physiological role of the channel has not been proved. The marine bacterium, Vibrio alginolyticus, is sensitive to osmotic stress and cell lysis occurs under osmotic downshock. We introduced an mscL gene into Vibrio alginolyticus, and the mechanosensitive channel with large conductance functions was found to allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 14 publications
(20 reference statements)
1
23
0
1
Order By: Relevance
“…Vibrio alginolyticus grows in marine environments and lyses when transferred to low osmolarity. Lysis can be prevented by expressing E. coli MscL from a plasmid (62). The genome of this organism, along with those for many other Vibrio species, has subsequently been sequenced.…”
Section: The Challenge Of Hypoosmotic Shockmentioning
confidence: 99%
“…Vibrio alginolyticus grows in marine environments and lyses when transferred to low osmolarity. Lysis can be prevented by expressing E. coli MscL from a plasmid (62). The genome of this organism, along with those for many other Vibrio species, has subsequently been sequenced.…”
Section: The Challenge Of Hypoosmotic Shockmentioning
confidence: 99%
“…Such apparent biochemical redundancy implied that observation of a phenotype might require the construction of a mutant lacking more than one channel protein. Preliminary support for the protective role of MscL was discovered by expressing the channel in Vibrio and observing protection from hypoosmotic shock (38). The discovery of the structural gene for MscS, the second major MS channel in E. coli, allowed this functional hypothesis to be tested (25).…”
Section: Overview Of Key Developmentsmentioning
confidence: 99%
“…Subsequent genetic experiments with the marine bacterium Vibrio alginolyticus revealed that the introduction of this gene alleviates cell lysis following osmotic downshock (17). Similar functions were also demonstrated in the Gram-positive bacteria Lactococcus lactis (7) and Bacillus subtilis (8).…”
mentioning
confidence: 71%
“…While the genetic basis for the failure of Salinispora strains to grow in low-osmotic-strength media has not been established, comparative genomics revealed a large family of highly duplicated polymorphic membrane proteins (PMPs), which were proposed to render cells unable to survive osmotic downshock (19). A more comprehensive bioinformatic analysis identified a larger pool of candidate marine adaptation genes and the lineage-specific loss of mscL (20), the product of which is a mechanosensitive channel that has been shown to alleviate cell lysis following osmotic downshock (17).…”
mentioning
confidence: 99%